Bridging Coursework and Publication: A Model to Help Students Produce Manuscripts Ready for Publication in Scientific Journals - Rahmat Rahmat; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2025)
The gap between academic coursework and publication readiness remains a significant challenge in higher education, where students often produce high-quality research assignments but lack the skills, confidence, and guidance to transform them into publishable manuscripts. This article introduces the Bridging Coursework and Publication model, a constructivist and publication-oriented pedagogical framework designed to guide students from coursework completion to manuscript submission. The model integrates scaffolded writing stages, peer review, publication simulation, reflective portfolios, and digital tool utilization to enhance students’ academic writing competence, publication literacy, and scholarly identity. A pilot implementation with undergraduate students in a research methodology course demonstrated substantial improvements in manuscript preparation, submission rates, and student engagement. The findings suggest that embedding publication-focused scaffolding within coursework can effectively bridge the gap between academic assignments and scholarly dissemination, fostering a culture of research and publication within higher education institutions. The model offers a replicable framework for curriculum designers, instructors, and policymakers aiming to enhance student research productivity and publication readiness.